Inhibitory Effects of Antimicrobial Photodynamic Therapy with Curcumin on Biofilm-Associated Gene Expression Profile of Aggregatibacter actinomycetemcomitans - Maryam Pourhajibagher; Nasim Chiniforush; Abbas Monzavi; Hamidreza Barikani; Mohammad Moein Monzavi; Shaghayegh Sobhani; Sima Shahbi; Abbas Bahador (Tehran University of Medical Sciences, 2018)
Objectives: Periodontitis is an inflammation of periodontal tissues that is caused by the biofilm of periodontal pathogens. Aggregatibacter actinomycetemcomitans (A. actinomycetemcomitans) is an opportunistic periodontopathogen that can be the cause of periodontal diseases via fimbriae as a virulence factor. In this study, we aimed to determine the expression level of A. actinomycetemcomitans rcpA gene as a virulence factor associated with biofilm formation after antimicrobial photodynamic therapy (aPDT) as a relatively new therapeutic modality. Materials and Methods: To determine sub-lethal doses of aPDT against A. actinomycetemcomitans ATCC 33384 strain, we used curcumin (CUR) as a photosensitizer at a final concentration of 40 µmol/ml, which was excited with a light-emitting diode (LED) at the wavelength of 450 nm. Quantitative real-time polymerase chain reaction (qRT-PCR) was then applied to monitor rcpA gene expression in A. actinomycetemcomitans. Results: 10-40 μmol/ml of CUR caused a signiﬁcant reduction in the growth of A. actinomycetemcomitans compared to control group (P<0.05). Also, the cell viability of A. actinomycetemcomitans was significantly decreased after more than four minutes of LED irradiation. Therefore, the sub-lethal dose of aPDT against A. actinomycetemcomitans was 5 μmol/ml of CUR with three minutes of LED irradiation at a ﬂuency of 180-240 J/cm2, which reduced the expression of the rcpA gene by approximately 8.5-fold. Conclusions: aPDT with CUR leads to decreased cell survival and virulence of A. actinomycetemcomitans. Thus, CUR-aPDT can be used as an alternative approach for the successful treatment of periodontitis in vivo.